2018
DOI: 10.1002/2017gl076763
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric Smoke With Unprecedentedly High Backscatter Observed by Lidars Above Southern France

Abstract: Extreme pyroconvection events triggered by wildfires in northwest Canada and United States during August 2017 resulted in vast injection of combustion products into the stratosphere. The plumes of stratospheric smoke were observed by lidars at Observatoire de Haute‐Provence (OHP) for many weeks that followed the fires as distinct aerosol layers with backscatter reaching unprecedentedly high values for a nonvolcanic aerosol layer. We use spaceborne CALIOP lidar to track the spatiotemporal evolution of the smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
179
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(205 citation statements)
references
References 29 publications
26
179
0
Order By: Relevance
“…According to the backward trajectories, the smoke traveled for about 7-10 days from western Canada to central Europe. This is in good agreement with the travel time derived from the spaceborne CALIPSO lidar observation presented by Khaykin et al (2018).…”
Section: Identification Of the Smoke Source Regionssupporting
confidence: 79%
See 4 more Smart Citations
“…According to the backward trajectories, the smoke traveled for about 7-10 days from western Canada to central Europe. This is in good agreement with the travel time derived from the spaceborne CALIPSO lidar observation presented by Khaykin et al (2018).…”
Section: Identification Of the Smoke Source Regionssupporting
confidence: 79%
“…The apparently ascending stratospheric soot layer (observed from 21 to 23 August) is the results of two different influences. Khaykin et al (2018) found that the smoke plumes ascended rapidly over the first few days following their injection into the upper troposphere with a rate of 2-3 km per day. This cross isentropic ascent was caused by radiative heating of smoke aerosols (Boers et al, 2010).…”
Section: Satellite-derived Products: Modis and Omi Retrievalsmentioning
confidence: 99%
See 3 more Smart Citations